A Critical Analysis on the Representation of Muslims in Britain in the Daily Mail Newspaper: Applying Discourse Analysis - BENHADDOU, MOUNA (International Journal of Language and Literary Studies, 2021)
The pervasiveness of mass media has become an inevitable side of our daily life; the ubiquity of the latter has allowed an unprecedented influx of information that is not necessarily value free and objective. The news that is present on our devices is full of ideological insinuations and is undoubtedly value laden. News corporations have spread enormously and reached different homes, especially with the advent of technology which permitted an outreach to distant various communities with a simple click. There are daily articles released claiming to have the most breaking and exclusive scoops of news that was not covered. Nevertheless, people find themselves overwhelmed and unable to differentiate between what is authentic and what is not. Not only that, but they ostensibly newspaper claim to have an innocent editorial line that matches worldwide media ethics, the truth is certainly a far cry from what is publicized. Every day, covert ideologies and doctrines are passed through news articles that target specific communities that either tend to vilify it exclude to perpetuate certain clichés and stereotypes about it. So this paper aims to critically analyze an article in the Daily Mail British newspaper which was written on British Muslim minorities, it address the issue of religion in a generalized way using extreme categorization, so as to infiltrate and increase division and animosity in British community. The paper uses a set of critical methods of discourses analysis to uncover hidden and even explicit messages ideologies in the article that. The analysis shows how implicit strategies are utilized to display a binary line between US and THEM. The THEM group is synonymous with extremism, irrationality and oppression against women whereas US is portrayed as a group serving justice and eradicate fanaticism and radicalism.